Earthen Architecture in Nordic Countries: Future Directions - Lorenzon Marta; Kinzel Moritz; Zoëga Guðný; Dabaieh Marwa (Open Archaeology, 2023)
Throughout prehistory, earthen architecture has played a pivotal role in establishing a sustainable and easily maintainable built environment, showcasing humanity's capacity to design and construct intricate structures using eco-friendly and cost-effective materials. This special issue underscores the enduring significance of earthen architecture in our historical and contemporary understanding of sustainable building practices.